2018
DOI: 10.1371/journal.pone.0185402
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prediction models for mortality and functional outcome following ischemic stroke: A systematic review and meta-analysis

Abstract: ObjectiveWe aim to identify and critically appraise clinical prediction models of mortality and function following ischaemic stroke.MethodsElectronic databases, reference lists, citations were searched from inception to September 2015. Studies were selected for inclusion, according to pre-specified criteria and critically appraised by independent, blinded reviewers. The discrimination of the prediction models was measured by the area under the curve receiver operating characteristic curve or c-statistic in ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 36 publications
1
76
2
1
Order By: Relevance
“…Several prognostic measures have been used to predict functional outcomes following thrombolytic therapy in patients with ischemic stroke. [9][10][11][12][13] These measures are based on clinical characteristics of the patient and provide cumulative evaluations for the management of poststroke treatment care. Accurate predictions of ambulatory functions are needed as well, so that clinicians can help patients set motor recovery goals to improve activities of daily living [14][15][16][17][18] following thrombolysis therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several prognostic measures have been used to predict functional outcomes following thrombolytic therapy in patients with ischemic stroke. [9][10][11][12][13] These measures are based on clinical characteristics of the patient and provide cumulative evaluations for the management of poststroke treatment care. Accurate predictions of ambulatory functions are needed as well, so that clinicians can help patients set motor recovery goals to improve activities of daily living [14][15][16][17][18] following thrombolysis therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple barriers to clinical translation of effective ischemic stroke therapeutics; one of which is the identification of an MRI-detectable structural parameter that can noninvasively predict functional outcome [14,[53][54][55]. Once identified and validated, these predictive biomarkers could then be utilized to assess clinical efficacy of novel therapeutics through divergence from established functional correlations [52].…”
Section: Discussionmentioning
confidence: 99%
“…Candidate predictors to be considered in the prediction models will be based on predictor variables as identified in previous systematic reviews in this field, 15 22 ease and reliability of measurement in clinical setting and theoretical association with the progression of outcomes. The number of variables required to ensure adequate power based on our target sample size (see below), to avoid overfitting and to encourage parsimony and applicability of the model in clinical practice will also be considered.…”
Section: Methodsmentioning
confidence: 99%
“…The systematic review and meta-analysis concluded that existing models have much potential and advised to build on previous work, as opposed to designing new models, in developing CPMs suitable for the long-term care setting. 15 Models predicting outcomes longitudinally, as opposed to predefined time points, may best support patient management and so we will build on work by colleagues in this area. 18 19 …”
Section: Introductionmentioning
confidence: 99%